BBC Sex-for-Grades-Report: Nigeria Tertiary Institutions ‘Crisis Management Strategies and Stakeholders’ Reactions - Fadipe, Israel Ayinla; Bakenne, Nuraen Adesola (The Journal of Society and Media, 2020)
Studies have already acknowledged sexual scandals as public relations nightmares of higher learning institutions. Therefore, we examined the crisis management strategies of Nigerian tertiary institutions and stakeholders' reactions after the British Broadcasting Corporation's sex-for-grades report. Adopting qualitative research, we analyzed 13 available press releases of institutions retrieved from some institutions' websites and sampled the opinions of 20 stakeholders comprising parents, students, and lecturers through a depth interviews. We used Coombs’ theory of crisis response strategies: denial, diminish, rebuild, and bolstering as thematic categories. We discovered that the institutions mostly used denial with diminished response strategy to blame societal decadence and scapegoat female students for and downplayed the severity of sexual harassment incidence by the institutions. More so, all the stakeholders distrust the local media's credibility in reporting sexual harassment cases. However, female students feel aggrieved that school administrations and the national government neglected them for failing to outlaw sexual harassment and severely punish offenders. Therefore, we recommend that considering stakeholders' perception of sexual harassment in Nigerian ivory towers, Nigerian higher educational institutions should not adopt a denial response strategy for sex scandal cases